Screening and partial characterization of bacteriocin from lactic acid bacteria in fish gastrointestinal tract - Rumjuankiat, Kittaporn; Pilasombut, Komkhae; Wangwibulkit, Somchai; Swetwiwathana, Adisorn (Asia-Pacific Journal of Science and Technology, 2017)
Screening and characterization of bacteriocin from lactic acid bacteria (LAB) in fish gastrointestinal tract were conducted. Four hundred isolates of LAB were screened from gastrointestinal tract of 6 fish species; Lates calcarifer (seabass), Channa striata (striped snake-head fish), Clarias batrachus (catfish), Orecochromis niloticus (nile tilapia), Barbonymus gonionotus (javanese barb) and Pangasianodon hypophthalmus (striped catfish). One effective isolate from seabass was able to produce bacteriocin and designated Sb2. Antibacterial activity test of cell free supernatant (CFS, pH 6.0) was performed against 17 bacteria target strains. CFS of Sb2 displayed growth inhibition of both spoilage and pathogenic bacteria. The maximum bacteriocin activity of 12,800 Au/ml against Lb. sakei subsp. sakei JCM 1157T was obtained at the optimum cultivation condition of 30°C for 18 hr. Its bacteriocin activity was partially inhibited by proteolytic enzyme of trypsin, a-chymotrypsin and proteinase K for 50%, 75% and 96.87%, respectively. It was stable at high temperature up to 100°C for 30 min. However, its activity was reduced to 50% (from 12,800 to 6,400 Au/ml) when it was incubated at 100°C for 60 min and 4°C for 7 days. As a result of this, bacteriocin produced from Sb2 could be used as biopreservative.